Сучасні методи надання персоналізованих рекомендацій в інформаційних системах - Мещан, К. А.; Міщеряков, Ю. В. (ХНУРЕ, 2022)
With the growing popularity of online stores, their assortment is also growing. Therefore, as a rule, problems arise that negatively affect both stores and customers. There is a large assortment here, but there are problems with it. A customer who saw in front of him a large number of products and their parameters may not immediately understand which of them he needs. However, unlike a regular store, there is no salesperson-consultant here. For this reason, new features have been introduced to increase the convenience of using online stores and increase profits. In particular, various personalized recommendations.